Sensitivity of Annual Weeds against Sulfentrazone 48 SC herbicide in Rice Cultivation (Bangladesh Rice Journal, 2018)
Herbicides are used successfully for weed control in rice fields for rapid effect, easier to application and low cost involvement in comparison to the traditional methods of hand weeding. Sulfentrazoneis a new pre-planting herbicide in Bangladesh. Field trials were conducted at Bangladesh Rice Research Institute (BRRI), Gazipur during Aman 2014 and Boro 2014-15 to evaluate the efficacy of sulfentrazone 48 SC on weed suppression and performance of transplanted rice. Treatments were Sulfentrazone 48 SC @ 150, 200 and 250 ml ha-1, pretilachlor 500 EC @ 1000 ml ha-1, weed free and unweeded control. Visual assessment indicated that this herbicide possesses high selectivity and not toxic to rice plants. The results revealed that the major weed flora associated with the transplanted rice was mainly comprised of two grasses, two sedges and four broadleaves in Aman 2014 and two grasses, two sedge and two broadleaves in Boro 2014-15. The most dominant weeds were Cyperus difformis, Echinochloa crus-galli, Scirpus maritimus and Monochoria vaginalis in both the growing seasons. Application of Sulfentrazone 48 SC @ 200 ml ha-1 was most effective to suppress weed density and dry masses in both the seasons resulting increased grain yield more than 50% as compared to unweeded control. Therefore, Sulfentrazone 48 SC @ 200 ml ha-1 should apply two or three days before plantingfor effectively control weeds in riceBangladesh Rice j. 2017, 21(1): 67-76